2015
DOI: 10.1002/jez.1935
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimentally increased in ovo lysozyme on egg hatchability, chicks complement activity, and phenotype in a precocial bird

Abstract: In birds, spectrum of egg white proteins deposited into the egg during its formation are thought to be essential maternal effects. Particularly, egg white lysozyme (LSM), exhibiting great between and within species variability, is considered to be essential for developing avian embryos due to its physiological, antimicrobial, and innate immune defense functions. However, there have been few studies investigating effects of LSM on early post-hatching phenotype, despite its broad physiological and protective rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 68 publications
(86 reference statements)
4
14
0
Order By: Relevance
“…Hatching success was reduced by low temperature but not by cycling. In fact, the cyclical treatment had the highest hatching success at 71%, although this was not significantly different from that for the control treatment (60%), and both were similar to previously reported hatching successes in Japanese quail (Copur et al 2010;Javurkova et al 2015). This result mirrors what was found with even longer cycling periods (8 h off-bouts) of incubation in Japanese quail (Callebaut 1990).…”
Section: Hatching Successsupporting
confidence: 88%
“…Hatching success was reduced by low temperature but not by cycling. In fact, the cyclical treatment had the highest hatching success at 71%, although this was not significantly different from that for the control treatment (60%), and both were similar to previously reported hatching successes in Japanese quail (Copur et al 2010;Javurkova et al 2015). This result mirrors what was found with even longer cycling periods (8 h off-bouts) of incubation in Japanese quail (Callebaut 1990).…”
Section: Hatching Successsupporting
confidence: 88%
“…Recent studies have identified more than 180 different egg white proteins in chicken eggs (Mann and Mann, 2011;Sun et al, 2017). Of these, lysozyme and ovotransferrin are the most abundant (Burley and Vadehra, 1989), having physiological (Giansanti et al, 2012;Javurkova et al, 2015; Krkavcová et al, 2018) and strong antimicrobial potential (Baron and Jan, 2011;Wellman-Labadie et al, 2008b). While lysozyme has significant bactericidal activity against Gram-positive as well as Gram-negative bacteria (Ibrahim et al, 2001;Wellman-Labadie et al, 2008a), ovotransferrin is primarily bacteriostatic via its iron-binding potential, forming an iron-deficient environment, inhibiting the growth of many microorganisms (Wu and Acero-Lopez, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both the alkaline pH ( Grizard et al, 2015 ) and the presence of antimicrobial proteins ( Shawkey et al, 2008 ; Horrocks et al, 2014 ) have been shown to significantly reduce the growth of microorganisms ( Board and Fuller, 1974 ) able to penetrate the eggshell and fundamentally affect egg hatchability ( Pinowski et al, 1994 ) and/or offspring phenotype ( Javůrková et al, 2014 ). In addition, many egg white proteins are thought to be important modulators of embryogenesis and immune phenotype; though few correlative studies ( Saino et al, 2002 , 2007 ; Bonisoli-Alquati et al, 2010 ; D′Alba et al, 2010 ) and only one experimental study ( Javůrková et al, 2015 ) have examined the effect of egg white proteins on the development and post-hatching phenotype of birds. Many egg white proteins also have binding sites specific to metal ions, such as Fe 3+ , or to vitamins, such as biotin, riboflavin or thiamine ( Muniyappa and Adiga, 1979 ; White and Merrill, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many egg white proteins also have binding sites specific to metal ions, such as Fe 3+ , or to vitamins, such as biotin, riboflavin or thiamine ( Muniyappa and Adiga, 1979 ; White and Merrill, 1988 ). Although the binding of these essential molecules to specific proteins prevents their use in the growth and proliferation of many pathogenic microorganisms, their presence is probably more important for proper development of the embryo ( Bonisoli-Alquati et al, 2010 ; Giansanti et al, 2012 ; Javůrková et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%